2019
DOI: 10.1136/bmjqs-2019-009936
|View full text |Cite
|
Sign up to set email alerts
|

Impact of structured interdisciplinary bedside rounding on patient outcomes at a large academic health centre

Abstract: BackgroundEffective communication between healthcare providers and patients and their family members is an integral part of daily care and discharge planning for hospitalised patients. Several studies suggest that team-based care is associated with improved length of stay (LOS), but the data on readmissions are conflicting. Our study evaluated the impact of structured interdisciplinary bedside rounding (SIBR) on outcomes related to readmissions and LOS.MethodsThe SIBR team consisted of a physician and/or advan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 14 publications
0
13
1
Order By: Relevance
“…Hospital readmissions are a worldwide, major health-care burden, with a negative impact on patient health, public health, and healthcare systems' associated national financial burden. Previous publications describe the heavy toll of hospital (non-surgical) re-admissions while the same researchers and others attempted various strategies for either predicting the risk for readmission and proactively reducing it (albeit with conflicting results) [5][6][7][8][9][10].…”
Section: The Need For Internal Medicine Personalization Hospital Lenmentioning
confidence: 99%
“…Hospital readmissions are a worldwide, major health-care burden, with a negative impact on patient health, public health, and healthcare systems' associated national financial burden. Previous publications describe the heavy toll of hospital (non-surgical) re-admissions while the same researchers and others attempted various strategies for either predicting the risk for readmission and proactively reducing it (albeit with conflicting results) [5][6][7][8][9][10].…”
Section: The Need For Internal Medicine Personalization Hospital Lenmentioning
confidence: 99%
“…International studies demonstrate that improved communication in interdisciplinary healthcare teams improves patients' depressive symptoms [4], reduces risks of postoperative complications and mortality [5], and improves assessment and patient management practices in oncology settings [6]. A recent study in acute care settings showed that enhancing communication between healthcare providers, patients, and their families using formal interactions significantly reduced 7-day readmission rates [7]. In contrast to informal communications (e.g., spontaneous discussions on the hallway), formal communications are planned and scheduled meetings to discuss and make decisions about care.…”
Section: Introductionmentioning
confidence: 99%
“…International studies demonstrate that improved communication in interdisciplinary healthcare teams improves patients' depressive symptoms [4], reduces risks of postoperative complications and mortality [5] and improves assessment and patient management practices in oncology settings [6]. A recent study in acute care settings showed that enhancing communication between healthcare providers, patients and their families using formal interactions signi cantly reduced 7-day readmission rates [7]. In contrast to informal communications (e.g., spontaneous discussions on the hallway), formal communications are planned and scheduled meetings to discuss and make decisions about care.…”
Section: Introductionmentioning
confidence: 99%